2004
DOI: 10.1002/dc.20052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and typing of HPV DNA by hybrid capture II in women with ASCUS, ASC‐H, LSIL, and AGC on ThinPrep® Pap tests

Abstract: Testing for human papillomavirus (HPV) DNA is now a viable option for the management of women with atypical squamous cells of undetermined significance (ASCUS). The utility of reflexive HPV DNA testing for women with a cytologic diagnosis of atypical glandular cells-not otherwise specified (AGC-NOS), ASCUS subtypes, and low-grade squamous intraepithelial lesion (LSIL) has not been well established. In the present investigation, reflex Hybrid Capture II HPV DNA testing results were evaluated for HPV prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
2
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 39 publications
1
17
2
3
Order By: Relevance
“…11 The frequency of HPV positivity among women with ASC-H cytology has been reported with a range of 38% to 84%. 5,[12][13][14][15][16][17] We found in our cohort that 64% of women with ASC-H had a positive HR-HPV test, which is lower than that obtained in the ALTS study (84%). 5 The rate of HR-HPV positivity in women with ASC-H can be varied among different age groups.…”
Section: Discussioncontrasting
confidence: 80%
“…11 The frequency of HPV positivity among women with ASC-H cytology has been reported with a range of 38% to 84%. 5,[12][13][14][15][16][17] We found in our cohort that 64% of women with ASC-H had a positive HR-HPV test, which is lower than that obtained in the ALTS study (84%). 5 The rate of HR-HPV positivity in women with ASC-H can be varied among different age groups.…”
Section: Discussioncontrasting
confidence: 80%
“…In previous studies, HPV was reported in 29%-61% in women with abnormal cytology results (21,22,23,24,25,26). In our study, the rate of HPV positivity in women with normal cervical cytology was 27%, refl ecting hospital based patients' accrual.…”
Section: Resultsmentioning
confidence: 89%
“…ASCUS cytology indicated that cytological-morphological changes were not benign; however, this did not meet the criteria for classification as squamous lesions, even though studies have shown that this type of cytological interpretation is highly related to characteristic subjective reading of Pap tests [37,38]. …”
Section: Discussionmentioning
confidence: 99%